Recurrent Urinary Tract Infection in Pregnancy Clinical Presentation and Feto-Maternal Outcome (Community Based Medical Journal, 2025)
There is a gap in substantial evidence regarding the increased likelihood of adverse outcomes associated with frequency of urinary tract infections (UTI) in pregnancy in our country. A cross-sectional study was conducted in the Department of Obstetrics & Gynaecology, BGB Hospital, Satkania, Chattogram, Bangladesh, from February 2023 to January 2024, to observe the maternal and fetal outcomes between respondents with single and recurrent episode of UTIs during their pregnancies. A total of 100 randomly selected women aged between 18 and 38 years having UTI during their pregnancy were enrolled in this study. Recurrent episode of UTI was observed in 38% cases. Urban women were more prevalent with the recurrence. Gestational diabetes (GDM), anaemia, cystitis were more commonly observed in recurrent UTI group. Higher proportions of preterm labor, preterm birth, low birth weight (LBW), neonatal sepsis, prematurity, intrauterine growth restriction (IUGR), and neonatal intensive care unit (NICU) admissions were evident more in recurrent UTI group compared to single episode of UTI group. Recurrence of UTI in pregnancy requires further evaluation for its risk factors during antenatal visits.  CBMJ 2025 January: Vol. 14 No. 01 P: 101-107